Green Accounting for Medium Enterprises through Participatory Action Research Study in Realizing a Sustainable Future - Fina Cholifiana (Fairness, 2025)
Objective: This study aims to identify and map the issues, and develop an effective and appropriate green accounting reporting model for medium-sized enterprises by examining the impact of green accounting implementation on financial performance and corporate sustainability.Research Design & Methods: This research uses a qualitative approach, using a systematic literature review method to analyze previous studies on green accounting. The analysis was conducted descriptively to synthesize insights on the relationship between green accounting practices, environmental sustainability, and financial performance.Findings: The results show that the application of green accounting has a positive effect on operational efficiency, transparency, and corporate competitiveness. It also motivates companies to implement more sustainable resource management strategies. In the hospitality sector, aligning green accounting practices with local cultural values enhances its implementation and effectiveness.Implications & Recommendations: These findings underscore the need for government support through regulations and incentives, such as subsidies or tax breaks, to encourage the adoption of green accounting, especially among SMEs. Educational institutions should provide training programs to improve technical understanding and awareness of environmental accounting. Companies are advised to integrate green accounting practices into their strategies to achieve economic and sustainability goals.Contribution & Value Added: This study contributes to the literature by providing a comprehensive understanding of the role of green accounting in improving financial and environmental performance. The study highlights the importance of contextual adaptation, especially in culturally diverse sectors, and offers actionable insights for policymakers, businesses, and educators.